Human plasma biomarker responses to inhalational general anaesthesia without surgery. (September 2020) - Deiner, Stacie; Baxter, Mark G.; Mincer, Joshua S.; Sano, Mary; Hall, James; Mohammed, Ismail; O'Bryant, Sid; Zetterberg, Henrik; Blennow, Kaj; Eckenhoff, Roderic
Abstract: Background: Postoperative neurocognitive disorders may arise in part from adverse effects of general anaesthetics on the CNS, especially in older patients or individuals otherwise vulnerable to neurotoxicity because of systemic disease or the presence of pre-existing neuropathology. Previous studies have documented cytokine and injury biomarker responses to surgical procedures that included general anaesthesia, but it is not clear to what degree anaesthetics contribute to these responses. Methods: We performed a prospective cohort study of 59 healthy volunteers aged 40–80 yr who did not undergo surgery. Plasma markers of neurological injury and inflammation were measured immediately before and 5 h after induction of general anaesthesia with 1 minimum alveolar concentration of sevoflurane. Biomarkers included interleukin-6 (IL-6), tumour necrosis factor alpha (TNF-α), C-reactive protein (CRP), and neural injury (tau, neurofilament light [NF-L], and glial fibrillary acidic protein [GFAP]). Results: Baseline biomarkers were in the normal range, although NF-L and GFAP were elevated as a function of age. At 5 h after induction of anaesthesia, plasma tau, NF-L, and GFAP were significantly decreased relative to baseline. Plasma IL-6 was significantly increased after anaesthesia, but by a biologically insignificant degree (<1 pg ml −1 ); plasma TNF-α and CRP were unchanged. Conclusions: Sevoflurane general anaesthesia without surgery, even in older adults, did not provoke an inflammatory state or neuronal injury at a concentration that is detectable by an acute elevation of measured plasma biomarkers in the early hours after exposure. Clinical trial registration: NCT02275026 .